PELANGGARAN HAK CIPTA LAGU DALAM BENTUK COVER DI MEDIA SOSIAL TELAAH SIYASAH SYARIYYAH - Barsyami, M Abid Tribuana; Maloko, M. Thahir (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2025)
This research aims to analyze forms of copyright infringement on song covers and their consequences as well as siyasi's views regarding copyright. The problem in this research is the use of songs on social media without legal permission from the copyright holder, causing losses to the creator. In answering this problem, we use a juridical approach, namely examining legal sources such as laws and regulations relating to copyright and a normative theological approach (syar'i), namely an approach based on the Koran and hadith. data collection methods in the form of secondary and primary materials, primary is done by directly reading sources related to copyright, namely UUHC, secondary is done by reading literature, scientific works, documents or books related to research. The results of the research show that the act of covering someone else's song for commercial purposes without permission from the creator as well as carrying out creation transformations and fixations is a form of copyright infringement. The legal consequences if the copyright holder feels disadvantaged and expresses objection, the perpetrator can be prosecuted civil law in the form of fines and criminal penalties. Siyasi's view regarding copyright is that the majority of scholars from the Maliki, Shafi'i and Hanbali schools of thought are of the opinion that copyright is equated with property ownership, using other people's creations without permission with the aim of self-interest or to obtain economic rights over someone else's creation. anything else is a disgraceful act.